A shell finite element for viscoelastically damped sandwich structures - Daya, El mostafa; Potier-Ferry, Michel (European Journal of Computational Mechanics, 2002)
In this paper, a shell finite element is proposed for viscoelastically damped sandwich structures, in which a thin viscoelastic layer is sandwiched between identical elastic layers. The sandwich finite element is obtained by assembling three elements throughout the thickness of the sandwich structure. Using specific assumptions and displacement continuity at the interfaces, one reduces to eight the number of degrees of freedom per node that are the longitudinal displacements of the elastic layers, the deflection and three rotations. The finite element computations have been compared with known analytical, numerical and experimental data concerning the vibrations of sandwich beams, plates and shells.